Reverse engineering approach in developing of a cam profile for internal combustion engine / Ahmad Razlan Yusoff and Rosdi Daud - Yusoff, Ahmad Razlan; Daud, Rosdi (2006)
Cam is a device converting a rotational movement to control reciprocating movement through its shape with very high accurate timing. The cam profile regarding displacement and angle information was not available for developing a cam profile model. An approach of reverse engineering was used to develop an original camshaft of internal combustion engine. The process began with finding the coordinate system of cam profile using Coordinate Measurement Machine (CMM). The information was applied to Computer Aided Design (CAD) and Computer Aided Manufacturing (CAM) software to prepare Computer Numerical Control (CNC) code. The code was generated to Wire cut Electro Discharge Machine (EDM) for fabricating cam. CMM, CAM and EDM capabilities and problems in developing cam model were also discussed. The result indicated the reverse engineering approach has capability in developing cam profile.